Road to Industrialized Africa : Role of Efficient Factor Market in Firm Growth - Nose, Manabu (Washington, D.C. : International Monetary Fund, 2018)
After a decade of rapid growth, industrialization has lost ground with shrinking manufacturing sector and high informality in Sub-Saharan Africa (SSA). This paper explores how land market and labor regulations affect factor allocative efficiency and firm performance in SSA. Using pooled data on firm balance sheets for 40 countries in SSA, the results identify significant land and labor misallocations due to limited market allocation of land and inappropriate regulatory policies. Using variations in ethnic diversity and the intensity of regulatory actions to peer firms at subnational level as instrumental variables, local average treatment effects show large productivity gains from factor reallocations, especially for marginally productive firms. Panel data results for Nigerian firms confirm factor market inefficiency as a principal driver of declining productivity, while showing that the 2011 minimum wage reform increased firm size. The results imply that improving formal regulation is critical to support firm growth at the stage of weak legal capacity, while informal sector monitoring gets effective as legal capacity develops.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet